(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Septic arthritis and soft tissue infection (SSTI) is a common infectious disease that can lead to rapid joint destruction and severe long-term sequelae. The increasing incidence of this disease in recent years, particularly in the elderly and patients with chronic underlying conditions, highlights the urgent need for studies aimed at early identification and enhanced treatment efficacy. Research Objective: To describe the clinical and microbiological characteristics of patients with septic arthritis and soft tissue infection treated at Hai Phong International General Hospital in 2025. Study subjects: 46 patients diagnosed with septic arthritis and soft tissue infection, who received inpatient treatment at the Department of Internal Medicine 2, Hai Phong International General Hospital from January 2025 to December 2025. Key Results: The mean age was 55,5 ± 18,2 years; , Common clinical manifestations included swelling (93.5%), pain (84.8%), restricted range of motion (82.6%), and fever (76.1%). Systemic Inflammatory Response Syndrome (SIRS) score ≥ 2 was observed in 56.5% of cases. The median C-reactive protein (CRP) level was 53.1(26,5 – 251,3) mg/L and the mean white blood cell (WBC) count was 14,2 ± 7,0 G/L. Microbiologically, Methicillin-Resistant Staphylococcus aureus (MRSA) was the predominant causative agent (30,4%). The most common underlying medical conditions recorded were diabetes mellitus (19,6%), gout (13.0%), and immunodeficiency or current use of immunosuppressive agents (10,9%). 56,5% of cases were associated with prior musculoskeletal procedures or preceding skin and soft tissue infections, while 43,5% had no identifiable port of entry. Factors significantly associated with a positive culture result included fever, the presence of SIRS, and soft tissue purulent discharge (p < 0,05).